Metamorphic evolution of mafic granulites from Tiyara area, Makrohar granulite belt, Singrauli district, Madhya Pradesh, India - Pandey V.; Dwivedi S.B. (My University, 2025)
The mafic granulite rocks from the Makrohar Granulite Belt of the Chotanagpur Granite Gneissic complex (CGGC) have been studied with reference to their petro-graphy, mineral chemistry and pressure–temperature (P–T) conditions of metamorphism. The common mine-ral assemblage observed within different thin sections is orthopyroxene–clinopyroxene–hornblende–plagioclase–biotite–quartz. The average P–T condition of the mafic granulites in the study area suggests a peak of meta-morphism at 799° ± 40°C/6.3 ± 0.9 kbar. However, the peak P–T estimate obtained from the conventional two-pyroxene thermobarometer is 5.83–6.47 kbar and 887° ± 62°C at a fixed pressure of 6 kbar, followed by post-peak P–T conditions of metamorphism at 590°–693°C/ 2.1–2.4 kbar. © 2022,Current Science.All Rights Reserved.